Docosahexaenoic Acid-Derived Fatty Acid Esters of Hydroxy Fatty Acids (FAHFAs) With Anti-inflammatory Properties - Kuda, Ondrej; Brezinova, Marie; Rombaldova, Martina; Slavikova, Barbora; Posta, Martin; Beier, Petr; Janovska, Petra; Veleba, Jiri; Kopecky, Jan; Kudova, Eva; Pelikanova, Terezie; Kopecky, Jan (Diabetes, 2016)
White adipose tissue (WAT) is a complex organ with both metabolic and endocrine functions. Dysregulation of all of these functions of WAT, together with low-grade inflammation of the tissue in obese individuals, contributes to the development of insulin resistance and type 2 diabetes. n-3 polyunsaturated fatty acids (PUFAs) of marine origin play an important role in the resolution of inflammation and exert beneficial metabolic effects. Using experiments in mice and overweight/obese patients with type 2 diabetes, we elucidated the structures of novel members of fatty acid esters of hydroxy fatty acids-lipokines derived from docosahexaenoic acid (DHA) and linoleic acid, which were present in serum and WAT after n-3 PUFA supplementation. These compounds contained DHA esterified to 9- and 13-hydroxyoctadecadienoic acid (HLA) or 14-hydroxydocosahexaenoic acid (HDHA), termed 9-DHAHLA, 13-DHAHLA, and 14-DHAHDHA, and were synthesized by adipocytes at concentrations comparable to those of protectins and resolvins derived from DHA in WAT. 13-DHAHLA exerted anti-inflammatory and proresolving properties while reducing macrophage activation by lipopolysaccharides and enhancing the phagocytosis of zymosan particles. Our results document the existence of novel lipid mediators, which are involved in the beneficial anti-inflammatory effects attributed to n-3 PUFAs, in both mice and humans.
Keywords: Insulin Resistance; Male; inzulinová rezistence; Lipopolysaccharides; Inflammation; buňky 3T3-L1; Obesity; kyseliny dokosahexaenové; lipopolysacharidy; fagocytóza; obezita; 3T3-L1 Cells; Adipocytes; Diabetes Mellitus, Type 2; mužské pohlaví; Macrophage Activation; bílá tuková tkáň; diabetes mellitus 2. typu; aktivace makrofágů; Adipose Tissue, White; zánět; kultivované buňky; tukové buňky; Animals; lidé; Fatty Acids, Unsaturated; Humans; Docosahexaenoic Acids; zvířata; estery; Linoleic Acid; myši inbrední C57BL; myši; Esters; Phagocytosis; Mice, Inbred C57BL; Cells, Cultured; antiflogistika; Anti-Inflammatory Agents; kyselina linolová; Mice; nenasycené mastné kyseliny